Mycotoxins in Feed and Food Chain Present Status and Future Concerns - Rossi, Filippo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The book deals with mycotoxins, their presence in various types of food, and how to prevent their presence in food . In addition to well-known molecules, such as aflatoxins or fumonisins, some contributors have dealt with emerging mycotoxins (e.g., alternaria toxins, botryodiplodin). Readers of the book can also find a new approach to reducing aflatoxins and fumonisins in food. In conclusion, the book presents both new mycotoxins and new information on old mycotoxins.